The Power of inclusion in family business - Trevinyo-Rodríguez, Rosa Nelly; Gallo, Miguel Ángel (Emerald Publishing Limited, 2022)
Nothing but good ownership makes long-lasting family companies. Yet, during our international consulting, research, and teaching engagements, we have encountered many ill-equipped next generation owners or owners-to-be, especially among women. We coined this phenomenon 'the daughters' inclusion challenge'. The Power of Inclusion in Family Business is a guide for grooming the next generation of responsible women owners, so they can thrive, achieve, and become leaders and wealth stewards in their multigenerational family businesses and family offices. We aspire to help enterprising families come across the power of including valuable women pertaining to the business-owning family in the family firm management, governance, ownership, and investment structures. In this book, outstanding global family business scholars and practitioners from 10 different countries, come together to serve a common purpose: provide novel insights, gender sensitive-consulting practices and culturally-adapted recommendations to advance the daughters' inclusion challenge and to shape a more inclusive family-in-business and family firm environment.